High Baseline Patient's Compared with Evaluator's Global Assessment Is Associated with Lower Retention and Remission Rates of First TNF Inhibitor in Psoriatic Arthritis Patients - Data from the EuroSpA Research Collaboration Network - Michelsen, Brigitte; Ornbjerg, Lykke Midtboll; Mann, Herman; Kvien, Tore; Nissen, Michael J.; Santos, Maria Jose; Hetland, Merete Lund (Wiley, 2019)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology/Association-of-Rheumatology-Professionals (ACR/ARP) -- NOV 08-13, 2019 -- Atlanta, GA